Environmental Radiation Dosimetry for school buildings, hospitals and health centers in Babil Governorate-Iraq using TL-technique - Al-Salihi, Abdalrahman; Abul-Hail, Riyadh Chasib; Badran, Hussain Ali (Journal of medical and pharmaceutical sciences, 2023)
The current research aims to evaluate the dose rate of gamma rays emitted from school buildings, hospitals and health centers in several locations in Babil Governorate using the TL method. To achieve the objectives of the research, measurements were taken at 49 school building sites and 29 hospital and health center sites using the thermal luminescence technique. The results of this study indicate that the inhabited areas within the environmental monitoring stations are places where the radiation is normal and the average dose rate in school buildings, hospitals and health centers to which humans are exposed is within the permissible limit.
Keywords: Gamma Rays; Radiation Dosimetry; Thermoluminescence Technique